Respuesta :

Answer:

see explanation

Step-by-step explanation:

Evaluate f(a) by substituting x = a into f(x)

f(a) = a - [tex]\frac{1}{a}[/tex]

Evaluate f(-[tex]\frac{1}{a}[/tex]) by substituting x = - [tex]\frac{1}{a}[/tex] into f(x)

f( - [tex]\frac{1}{a}[/tex]) = - [tex]\frac{1}{a}[/tex] - [tex]\frac{1}{-\frac{1}{a} }[/tex]

                                    = - [tex]\frac{1}{a}[/tex] - ( 1 × - [tex]\frac{a}{1}[/tex])

                                   = - [tex]\frac{1}{a}[/tex] + a = a - [tex]\frac{1}{a}[/tex]

Hence f(a) = f(- [tex]\frac{1}{a}[/tex])

ACCESS MORE